Sazmani Mujahidini Khalq dar dami tavahhumati librali . ; . Mujahidin va ittihadi amali anan ba libralha dar jarayani intikhabati Majlisi Shurai-yi Milli (Sazmani Paykar dar Rahi Azadi-yi Tabaqah-yi Kargar)
The People's Mujahidin Organisation trapped in liberal illusions; The Mujahidin and their alliance with the Liberals during the during the parliamentary elections.